2020
DOI: 10.3390/ijerph17217928
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Level during Pregnancy in South Africa: A Facility-Based Cross-Sectional Study

Abstract: Physical activity participation during pregnancy confers many maternal and foetal health benefits to the woman and her infant and is recommended by various health bodies and institutions. However, in South Africa, scant information exists about the physical activity status and its determinants among pregnant women. The aim of this study was to assess the physical activity level and associated factors among pregnant women. This cross-sectional study enrolled 1082 pregnant women attending public health facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 69 publications
0
36
0
1
Order By: Relevance
“…However, research has found that physical activity in women decreases from prepregnancy to pregnancy 11,12 . In fact, the majority of pregnant women do not meet the recommended amount of duration for daily physical activity 13–15 . The reported reasons include physical discomfort, fatigue, lack of time or motivation, and concerns about safety for the women and/or fetus 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, research has found that physical activity in women decreases from prepregnancy to pregnancy 11,12 . In fact, the majority of pregnant women do not meet the recommended amount of duration for daily physical activity 13–15 . The reported reasons include physical discomfort, fatigue, lack of time or motivation, and concerns about safety for the women and/or fetus 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study explored the experiences of Taiwanese mothers after a successful ART treatment. The women interviewed reported less physical activity overall, to the extent of even choosing to stay at home during pregnancy [16]. Even if no direct comparison between women who became pregnant in a natural way and women after ART was conducted, the findings confirmed that the overall physical activity is reduced in the group after ART.…”
Section: Discussionmentioning
confidence: 80%
“…However, prenatal physical activity and exercise have not been widely studied within the context of South Africa. To address this lack, a prenatal physical activity intervention strategy has been developed specifically for South Africa and is on the first empirical findings [24][25][26][27]. This timely move provides a unique contribution to, and lays the groundwork for, future prenatal physical activity intervention strategies, not only in the Eastern Cape Province but throughout South Africa as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-stage approach was utilized, with Phase I focussing on the empirical findings on facilitators of or barriers to prenatal physical participation in Buffalo City Municipality, Eastern Cape Province, which then lays the groundwork for the development of a prenatal physical activity strategy [24][25][26][27]. Therefore, the results of the studies above have provided us with guidance into developing an effective prenatal physical activity strategy that promotes the practice of prenatal physical activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation